ON PHENOMENON OF ELECTRON’S RUNAWAY IN PARTIALLY IONIZED NON-IDEAL PLASMA - Turekhanova, K.M. (Recent Contributions to Physics, 2008)
The effect of electrons runaway in partially ionized hydrogen plasma is investigated on the basis of the pseudopotential models. The electrons runaway conditions were determined. Dependences of electron free path on the plasma density and coupled parameter were obtained. It has been shown that if the quantum-mechanical and screening effects in non-ideal partially ionized plasma are taken into consideration, then collision frequency curve for electrons would has maxima, also free path curves for electrons would has minima.